Pemanfaatan Kulit Batang Tumbuhan Sikkam (Bischofia javanica Blume) Sebagai Bahan Pembuatan Dayon Nabinatur - Panjaitan, Elida Octavia (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2023)
Utilization of sikkam bark (Bischofia javanica Blume), has benefits as a mixed ingredient in the manufacture of Dayok Nabinatur. There are plants used to make the food, namely: Sikkam wood, grated coconut, galangal, ginger, lemongrass, shallots, garlic, bay leaves, peppercorns, red chilies. Sikkam also has benefits as herbal medicines. Seikkam is also a tree that has a height of 40m, a trunk diameter of 95-150cm, the trunk is straight, usually hard and strong. The leaves are green in color, 4-8 inches long and 7-22 mm thick, the leaf shape is oval, three-lobed and tapers to the tip of the leaf. The location of the leaves is spiral/circular, has long petioles (3-8 inches) edges serrated to finely serrated, leaf pinnate, glossy upper side. The fruit does not break down, is round, gummy, 1.2-1.5 cm in diameter, bluish-black when ripe, with 1-2 seeds in each chamber, oval brown seeds, 5 mm long. Keywords: Sikkam, Traditional Food, Dayok Nabinatur